DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF PIPERAQUINE PHOSPHATE AND DIHYDROARTEMISININ IN BULK - Deokate, Uday A.; Nawale, Rajesh B.; Gorde, Anjali Macchindra (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
High Performance Liquid Chromatography (HPLC) methods are described for determination of drugs as a single or in combination in bulk or pharmaceutical formulation. The objective of the present study was to develop and validate novel, accurate, sensitive, precise, rapid and isocratic reverse Phase HPLC (RP-HPLC) method for the simultaneous determination of Piperaquine phosphate and Dihydroartemisinin in bulk because no method is available for simultaneous estimation of these drugs. The separation was achieved on GRACESMART RP-18 column (250 mm Ã— 4.6 mm, 5Î¼m) with mobile phase consisting of 10 mM Ammonium acetate (pH4.6, adjusted with Acetic acid): Methanol (15:85 % v/v) at a flow rate of 1.2 ml/min. UV detection at 220 nm. PQP and DHA obeyed linearity in the concentration range of 5-25 Î¼g/ml (r2 = 0.9993) and 5-25 Î¼g/ml (r2 = 0.9987) respectively. The asymmetric factors were found to be 1.17 for PQP and 1.2 for DHA. The developed method was validated as per ICH guidelines fulfill all the acceptance criteria and can be use for routine analysis.